Awake craniotomy in brain tumors - Technique systematization and the state of the art - KRAMBEK,MÁRCIO CARDOSO (2021)
ABSTRACT The anesthesia for awake craniotomy (AC) is a consecrated anesthetic technique that has been perfected over the years. Initially used to map epileptic foci, it later became the standard technique for the removal of glial neoplasms in eloquent brain areas. We present an AC anesthesia technique consisting of three primordial times, called awake-asleep-awake, and their respective particularities, as well as delve into the anesthetic medications used. Its use in patients with low and high-grade gliomas was favorable for the resection of tumors within the functional boundaries of patients, with shorter hospital stay and lower direct costs. The present study aims to systematize the technique based on the experience of the largest philanthropic hospital in Latin America and discusses the most relevant aspects that have consolidated this technique as the most appropriate in the surgery of gliomas in eloquent areas.